2020
DOI: 10.1186/s40900-020-00232-3
|View full text |Cite
|
Sign up to set email alerts
|

“They heard our voice!” patient engagement councils in community-based primary care practices: a participatory action research pilot study

Abstract: Background Patient engagement could improve the quality of primary care practices. However, we know little about effective patient engagement strategies. We aimed to assess the acceptability and feasibility of embedding advisory councils of clinicians, managers, patients and caregivers to conduct patient-oriented quality improvement projects in primary care practices. Methods Using a participatory action research approach, we conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…Action research groups, allowing clinicians to act as researchers, calibrate approaches and share best practice Staff engagement [ 63 , 64 ]. Action Research Groups [ 64 , 65 ] Patient participatory councils These groups provide an opportunity to bring professionals, managers and clinical and non-clinical staff together to ensure healthcare is patient-oriented and maximise patient involvement and choice Patient engagement and participatory action research group [ 66 ] Skills workshops Workshops and train the trainer workshops offer opportunities to bolster skills and embed this into practice by training champions Train the trainer workshops [ 57 ]. Skills workshop [ 67 , 68 ] Simulation and role play Utilising the role of simulated or unstructured role-play to explore complex scenarios in mental health in safe no-risk environments Simulation [ 51 ].…”
Section: Enhancing Psychological Safetymentioning
confidence: 99%
“…Action research groups, allowing clinicians to act as researchers, calibrate approaches and share best practice Staff engagement [ 63 , 64 ]. Action Research Groups [ 64 , 65 ] Patient participatory councils These groups provide an opportunity to bring professionals, managers and clinical and non-clinical staff together to ensure healthcare is patient-oriented and maximise patient involvement and choice Patient engagement and participatory action research group [ 66 ] Skills workshops Workshops and train the trainer workshops offer opportunities to bolster skills and embed this into practice by training champions Train the trainer workshops [ 57 ]. Skills workshop [ 67 , 68 ] Simulation and role play Utilising the role of simulated or unstructured role-play to explore complex scenarios in mental health in safe no-risk environments Simulation [ 51 ].…”
Section: Enhancing Psychological Safetymentioning
confidence: 99%
“…Previous research has recommended combining the two methods, so having both patient representatives as well as using other methods such as patient questionnaires, to learn more about the perspectives of a large group of patients. 33 Furthermore, in the literature, there are different opinions on the level of professionalism that is required from patients to participate at the collective level. Some studies stipulate the importance of training the patients, 9,[34][35][36][37][38] while others criticize this need of training, since this would lead to 'proto-professionalism' of patients participating in such projects and minimizes the representativeness of patients.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31] Literature is sparse on how PMHs can help advance PCM methods to support effective use of PCM in teambased care. While there are studies on incorporating patient voices, 32,33 and patient-reported experiences and outcomes [34][35][36] in evaluating PMH performance, we are not aware of studies that examine how PMHs can help advance PCM methods, particularly in resource-limited settings. 37 Thus, there is a need for new PCM methods that take into account the nuances in the PMH model of teambased care, and use of digital tools for team-based care.…”
Section: Digital Technologiesmentioning
confidence: 99%